ANGPTL3 Overexpression Suppresses the Development of Oncogenic Properties in Renal Cell Carcinoma via the Wnt/β-Catenin Signaling Pathway and Predicts Good Prognosis. (25th August 2021) - Zhang, Yu-jian; Zhang, Lin; Feng, Fei; Cao, Qi-feng
Abstract : Angiopoietin-like 3 (ANGPTL3), which is involved in new blood vessel growth, has been reported to exhibit an abnroaml expression in many different cancers. However, the expressing pattern and functions of ANGPTL3 renal cell carcinoma (RCC) were rarely reported. In this study, we observed that ANGPTL3 expression was distinctly downregulated in both RCC specimens from TCGA datasets and cell lines. Survival assays also revealed that patients with low ANGPTL3 expression exhibited a shorter overall survival and disease-free survival than those with high ANGPTL3 expression. Cell counting kit-8 (CCK-8) assay, Colony formation assay, and flow cytometry showed that overexpression of ANGPTL3 distinctly suppressed the proliferation of RCC cells, and promoted apoptosis. Transwell assays and Wound healing assays revealed that ANGPTL3 upregulation suppressed the migration and invasion of RCC cells. Then, we explored whether ANGPTL3 dysregulation influenced the alteration of Wnt/ β -catenin signaling using TOP/FOP flash reporter assays and western blot. The results showed that overexpression of ANGPTL3 distinctly suppressed the activity of Wnt/ β -catenin signaling. Overall, our results confirmed that overexpression of ANGPTL3 was related to the malignancy and good prognosis of RCC patients, and ANGPTL3 upregulation inhibited the tumor proliferation and metastasis via the Wnt/ β -catenin pathway. ANGPTL3 may be a novel therapeutic target and a prognostic biomarker for RCC patients.